2022-RA-760-ESGO Predictive model of severe complications in patients who underwent an open gynecological cancer surgery on an enhanced recovery after surgery (ERAS) program. (20th October 2022) - Fumagalli, Diletta; Grassi, Tommaso; Bazzurini, Luca; Bianchi, Tommaso; Procaccianti, Chiara; Gili, Mauro Angelo; Martino, Giampaolo Di; Trezzi, Gaetano; Vecchione, Francesca; Meo, Maria Letizia Di; Zambetti, Benedetta; de Vicari, Desirée; et al.
Abstract : Introduction/Background: Enhanced Recovery After Surgery (ERAS) is a global multimodal perioperative care initiative designed to achieve early recovery after major surgery. Our primary objective was to analyze the postoperative outcomes after open gynecological cancer surgery on an ERAS program and to design a predictive model of severe complications after surgery. Methodology: We retrospectively reviewed patients undergoing open surgery for suspected gynecological malignancy and managed according to the ERAS guidelines from January 1st, 2019 to December 31st, 2019, at a tertiary-care center in Monza, Italy. Surgical Complexity Score (SCS), Clavien-Dindo Classification (CDC) of complications and a Comprehensive Complication Index (CCI) were applied for each patient. Association between patient-, disease- and surgical-variables and severe postoperative complications (defined as CCI ≥26.2 events) were estimated using a uni- and multivariable logistic regression model. Factors associated with severe postoperative complications were used to construct a predictive model and nomogram. Results: One hundred and fifty-eight patients who underwent an open surgery were included in the study: 86 ovarian, 28 cervical, 39 uterine and 5 non-gynecological cancers. Overall, 8.2% of patients experienced a CDC grade IIIA-V complication, while 13.3% had a CCI ≥26.2. The median CCI was 8.7 [IQR 0–20.9]. Cancer type, number of comorbidities, blood loss during surgery and SCS were independent predictors of severe postoperative complications after open gynecological cancer surgery. Conclusion: The application of an ERAS program in open gynecological cancer surgery is safe and results in an acceptable complication rate. The risk of severe postoperative complications may be predicted using our risk-model. This may help the clinician in personalizing care for each patient. Further prospective evaluations of this model are needed.